Analysis of students’ learning interest in biology subject at SMAN 1 Panai Hulu in the independent curriculum era - Risma Delima Harahap; Sakinah Ubudiyah Siregar; Anggi Pradana (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
Interest greatly determines student learning outcomes both academically and non-academically. Students' interest in learning decreased due to factors in learning methods that were less memorable and learning media factors that were less attractive. This study aims to describe the learning interest of class XI students at SMAN 1 Panai Hulu in biology subject. Subjects in the study were students XI IPA1, XI IPA2 and XI IPA3, with a total of 105 people. This type of research is a qualitative descriptive research. Data collection techniques using questionnaires, observation, and interviews. The results of research that has been carried out with four indicators are obtained, namely the feeling of pleasure of students in participating in learning by 75.77%, student attention to learning by 70.78%, student interest in learning by 74.04%, student involvement in learning by 73.91 %. Based on these results, it can be concluded that students' interest in learning biology in class XI IPA1, XI IPA2 and XI IPA3 at SMAN 1 Panai Hulu is high. Even though students' learning interest is high, student activity is still influenced by the completeness of learning media.AbstrakMinat sangat menentukan hasil belajar siswa baik secara akademik maupun non akademik. Minat belajar siswa menurun dikarenakan faktor cara belajar yang kurang berkesan dan faktor media pembelajaran yang kurang menarik. Penelitian ini bertujuan untuk mendeskripsikan minat belajar siswa kelas XI di SMAN 1 Panai Hulu pada mata pelajaran biologi. Subjek dalam penelitian adalah siswa XI IPA1, XI IPA2 dan XI IPA3, dengan total sebanyak 105 orang. Jenis penelitian ini adalah penelitian deskriptif kualitatif. Teknik pengumpulan data menggunakan lembar angket, observasi, dan wawancara. Hasil penelitian yang telah dilakukan dengan empat indikator didapatkan yaitu perasaan senang siswa dalam mengikuti pembelajaran sebesar 75,77%, perhatian siswa terhadap pembelajaran sebesar 70,78%,  ketertarikan siswa terhadap pembelajaran sebesar 74,04%, keterlibatan siswa terhadap pembelajaran sebesar 73,91%. Berdasarkan hasil tersebut dapat disimpulkan minat belajar siswa kelas XI IPA1, XI IPA2 dan XI IPA3 di SMAN 1 Panai Hulu terhadap pembelajaran biologi adalah sangat tinggi. Meskipun minat belajar peserta didik tinggi, keaktifan peserta didik masih dipengaruhi oleh kelengkapan media pembelajaran.